The hydrogen bond rotation of confined water affected by quantum resonance tunnelling - Yang, Xinrui; Jin, Le; Zhu, Yu; Zhang, Zhiyuan; Liu, Rui; Wang, Zhigang (Frontiers in Physics, 2022)
In this work, we report quantum tunnelling effects on the confined water chain flipping, different from the spatial size and even electronic correlation effects of the confinement environment. First-principles calculations and analyses confirm that quantum tunnelling from the water chain itself enhances the hydrogen bond rotation. Importantly, the neglected resonant tunnelling can result in tunnelling rotation of hydrogen bonds with a probability close to 1 through the provided 0.6 eV energy, while the probability of generally recognized sequential tunnelling is only 10-6. Not only that, compared to sequential tunnelling, resonant tunnelling leads to a 20 K higher flipping temperature of the water chain. Additionally, the ratio of the resonant tunnelling probability to the thermal disturbance probability at 200 K is at least ten times larger than that of sequential tunnelling, which further illustrates the enhancement of hydrogen bond rotation brought about by resonant tunnelling.